2016
DOI: 10.1038/nplants.2016.33
|View full text |Cite
|
Sign up to set email alerts
|

Vascular-mediated signalling involved in early phosphate stress response in plants

Abstract: Depletion of finite global rock phosphate (Pi) reserves will impose major limitations on future agricultural productivity and food security. Hence, modern breeding programmes seek to develop Pi-efficient crops with sustainable yields under reduced Pi fertilizer inputs. In this regard, although the long-term responses of plants to Pi stress are well documented, the early signalling events have yet to be elucidated. Here, we show plant tissue-specific responses to early Pi stress at the transcription level and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
141
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(151 citation statements)
references
References 46 publications
10
141
0
Order By: Relevance
“…The mobile macromolecules currently cover 14 different species and ecotypes, namely A. thaliana Col-0, A. thaliana PED (13), Apium graveolens (celery) (15), Antirrhinum majus (snapdragon) (16), Ricinus communis (castor bean) (17), Cucumis melo (melon) (18), Citrullus lanatus (watermelon) (19), Cucumis sativus (cucumber) (19), Cucurbita maxima (pumpkin) (20), Cucurbita moschata (winter squash) (21), Vitis spp (grapevine species) (22), Oryza sativa (rice) (23), Solanum lycopersicum (tomato) (24) and Solanum tuberosum (potato) (11). Identification of the mobile macromolecules was based on different experimental methods, such as analysis of the phloem exudate/sap (15,17,18,25,26), the presence of distinguishable transcripts found in parasitic plants and their host plants (13,14) or by single nucleotide polymorphisms (SNPs) in mRNAs from heterografted plants or from grafted mutant/wild-type plants (13,22,27,28). The mobile macromolecule data was derived from ESTs, RNA sequencing (RNA-seq), microarrays and proteomics.…”
Section: Methodsmentioning
confidence: 99%
“…The mobile macromolecules currently cover 14 different species and ecotypes, namely A. thaliana Col-0, A. thaliana PED (13), Apium graveolens (celery) (15), Antirrhinum majus (snapdragon) (16), Ricinus communis (castor bean) (17), Cucumis melo (melon) (18), Citrullus lanatus (watermelon) (19), Cucumis sativus (cucumber) (19), Cucurbita maxima (pumpkin) (20), Cucurbita moschata (winter squash) (21), Vitis spp (grapevine species) (22), Oryza sativa (rice) (23), Solanum lycopersicum (tomato) (24) and Solanum tuberosum (potato) (11). Identification of the mobile macromolecules was based on different experimental methods, such as analysis of the phloem exudate/sap (15,17,18,25,26), the presence of distinguishable transcripts found in parasitic plants and their host plants (13,14) or by single nucleotide polymorphisms (SNPs) in mRNAs from heterografted plants or from grafted mutant/wild-type plants (13,22,27,28). The mobile macromolecule data was derived from ESTs, RNA sequencing (RNA-seq), microarrays and proteomics.…”
Section: Methodsmentioning
confidence: 99%
“…This observation might lead us to assume that most of the mobile transcripts might have a signalling function. However, a gene ontology (GO) analysis revealed that the translational products of mobile mRNAs do not have a functional bias regarding signalling or biotic or abiotic stresses (Thieme et al ., ; Calderwood et al ., ; Zhang et al ., ).…”
Section: Classes Of Phloem Transported Rnas and Their Functionmentioning
confidence: 97%
“…Next Generation Sequencing techniques combined with heterografting approaches, in which related but genetically distinct species were grafted, revealed that 2006 poly‐A RNAs move between Arabidopsis rootstocks and scions (Thieme et al ., ). Similar results were obtained with heterografted cucumber/watermelon and grapevine species (Yang et al ., ; Zhang et al ., b). Here, >1000 graft‐mobile mRNAs were identified in various heterologous scion tissues (Table ).…”
Section: Classes Of Phloem Transported Rnas and Their Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we refer to graft‐mobile ‘signals’ as molecules that are capable of acting at a distance to influence organismal processes, such as developmental transitions, morphological responses, nutrient acquisition, and biotic interactions. The extent to which mobile macromolecules function as signals within the plant communication network (Zhang et al ., ) remains an open question (Calderwood et al ., ; Lee & Frank, ; Morris, ). Therefore, we suggest the use of a separate term, the ‘mobileome’, to discuss the mass collection of RNAs and proteins that have been shown to move, but do not yet have well‐defined functions in long‐distance communication.…”
Section: Defining Mobile Signalsmentioning
confidence: 99%